2002
DOI: 10.1016/s1010-7940(02)00069-6
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive endoscopic repair of pectus excavatum

Abstract: The minimally invasive endoscopic pectus repair is safe and effective and currently our procedure of choice for primary pectus excavatum in all ages. Endoscopic visualization facilitates the safe creation of the retrosternal tunnel. Short-term results have been excellent. Further follow-up will be necessary to determine long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…The ages of the patients who wereoperated on by the MIrPE procedurew as 5y earsh igher (14)(15)(16) years) at the end of our series than at the beginning. Ahigher age decreases the incidence of relapses after the bar removal.…”
Section: Discussionmentioning
confidence: 76%
“…The ages of the patients who wereoperated on by the MIrPE procedurew as 5y earsh igher (14)(15)(16) years) at the end of our series than at the beginning. Ahigher age decreases the incidence of relapses after the bar removal.…”
Section: Discussionmentioning
confidence: 76%
“…Thirty-two [4,38] publications with 2997 patients (median: 53; range: 10-947) reported results following MIRPE with the metallic bars in situ (Table 1). Twenty-three publications [4,6,11,[13][14][15][16][17]21,[23][24][25][26][27][30][31][32][33][34][35][36][37][38] with 1393 (median: 36; range: 6-521) patients reported results after MIRPE completion with the bar(s) having been removed (Table 2). One study reported the results of MIRPE in 50 patients in whom a previous, conventional repair of PE had failed (redo surgery) [27].…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies [6,7,11,13,15,[20][21][22][23]25,27,29,31,32,34,36,39,41] (Table 1) report from a mixed population from all three age groups. Five publications [4,[8][9][10]18] report from a mixed paediatric and adolescent population.…”
Section: Age At Time Of Mirpementioning
confidence: 99%
“…Through the years, minor modifications have been applied, but the main idea of the method remained the same and the Ravitch repair was the treatment of choice until the mid-1990s. Since its introduction by Nuss et al [4] in 1997, the minimally invasive repair of pectus excavatum (MIRPE) has been gaining acceptance worldwide among surgeons and patients [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%